Persepsi Masyarakat Mengenai Pencegahan DBD (Demam Berdarah Dengue) Di Wilayah Sungai Lulut Banjarmasin Berdasarkan Teori TPB (Theory Of Planned Behavior) - Aisya, Rihaddatul; Melviani, Melviani; Komalia, Risyda (LPPM Universitas Sari Mulia, 2025)
Background : Dengue Hemorrhagic Fever (DHF) is a disease that continues to increase from year to year very quickly. Prevention of dengue fever urgently requires the involvement of various elements, one of which is the community. Public perception of the prevention of Dengue Hemorrhagic Fever (DHF) can be analyzed based on the theory of Planned Behavior (TPB). Objective : To find out the perception of the community in the Lulut River Region regarding the prevention of Dengue Hemorrhagic Fever (DHF) based on the theory of Planned Behavior (TPB). Methods : Observational research analysis with cross sectional. Sampling was carried out by purposive sampling technique. The research sample amounted to 100 respondents. Data was obtained by questionnaires distributed to the community and analyzed by chi-square test. Results : 55% of the respondents had sufficient behavior, 46% of the respondents had a good attitude, 49% of the respondents had sufficient subjective norms, and 54% of the respondents had sufficient behavioral control. The attitude variable had a relationship with dengue prevention behavior of 0.014 (p<0.05), the norm variable had a relationship with dengue prevention behavior of 0.019 (p<0.05), the behavioral control variable had a relationship with dengue prevention behavior of 0.012 (p<0.05. Conclusion : The results of the test in this study showed that there was a relationship between attitudes, subjective norms and behavioral control with community behavior in the prevention of Dengue Hemorrhagic Fever (DHF) based on the Theory of Planned Behavior